(untitled) (Rudarsko-geološko-naftni zbornik, 2018)
Hydraulic parameters affects behaviour of various ions in soils. The goal of this paper was to get better understanding of relationship between physical and chemical properties and soil permeability at the location of case study profile Velika Gorica, based on the physical and chemical data. Soil profile is situated in the Eutric Cambisol of the Zagreb aquifer, Croatia. Zagreb aquifer represents the only source of potable water for inhabitants of the City of Zagreb and Zagreb County. Based on the data obtained from particle size analysis, soil hydraulic parameters and measured water content, unsaturated hydraulic conductivity values were calculated for the estimation of soil profile permeability. Soil water retention curves and unsaturated hydraulic conductivities are very similar for all depths because soil content does not change significantly through the depth. Determination of anions and cations on soil samples was performed using the method of ion chromatography. Results showed decrease of ions concentrations after 0.6 m depth. SAR distribution in the soil profile shows that SAR values are not significantly changing at the soil profile. The highest CEC and EC values are determined in horizon Bw developed in 0.6 m depth which is consistent with highest SAR value and ions concentrations. All results suggest that physical and chemical properties of investigated profile are in relationship with soil permeability.